ChemInform Abstract: A Metal‐Free Synthesis of N‐Aryl Carbamates under Ambient Conditions. Issue 2 (23rd December 2015) - Guo, Wusheng; Gonzalez‐Fabra, Joan; Bandeira, Nuno A. G.; Bo, Carles; Kleij, Arjan W.
Abstract: This method yields the title N‐aryl carbamates in good yields from cyclic carbonates under mild metal‐free conditions using TBD as an effective and cheap organocatalyst.